2017
DOI: 10.1155/2017/1407506
|View full text |Cite
|
Sign up to set email alerts
|

R229Q Polymorphism of NPHS2 Gene in Group of Iraqi Children with Steroid-Resistant Nephrotic Syndrome

Abstract: Background. The polymorphism R229Q is one of the most commonly reported podocin sequence variations among steroid-resistant nephrotic syndromes (SRNS). Aim of the Study. We investigated the frequency and risk of this polymorphism among a group of Iraqi children with SRNS and steroid-sensitive nephrotic syndrome (SSNS). Patients and Methods. A prospective case control study which was conducted in Al-Imamein Al-Kadhimein Medical City, spanning the period from the 1st of April 2015 to 30th of November 2015. Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…Moreover, Shatha et al (22) , Phelan et al (23) , Behnam et al (24) were in contrast to our findings. They concluded that polymorphism R229Q of NPHS2 gene is prevalent in Iraqi children with SRNS and SSNS.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, Shatha et al (22) , Phelan et al (23) , Behnam et al (24) were in contrast to our findings. They concluded that polymorphism R229Q of NPHS2 gene is prevalent in Iraqi children with SRNS and SSNS.…”
Section: Discussioncontrasting
confidence: 99%
“…Ali et al. established male predominance with statistical significance in case of p.R229Q [ 31 ]. Similar findings were observed in studies of different region [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Steroid responsive NS (SSNS) was regarded as complete remission achieved with steroid therapy. Steroid-resistant NS (SRNS) was regarded as failure to achieve remission following 4-week prednisone 60 mg/m2 followed by three methylprednisolone pulses [7], [8].…”
Section: Methodsmentioning
confidence: 99%